Α Revision of the Genus Bryobia in Greece (Acari: Tetranychidae) - Hatzinikolis, E.N.; Emmanouel, N.G. (ENTOMOLOGIA HELLENICA, 1991)
The genus Bryobia from Greece is revised and a key to 16 species is provided. Three new species, B. caricae, B. cerasi and B. siliquae, are described and illustrated. Four species, B. artemisiae Bagdasarian, B. convolvulus Tuttle and Baker. B. vasiljevi Reek and B. watersi Manson are recorded for the first time in this country. Information on the hosts, distribution and economic importance is presented for each species. Some of the hosts and damage symptoms are recorded for the first time.